2011
DOI: 10.1002/icd.759
|View full text |Cite
|
Sign up to set email alerts
|

Task Palatability, But Not Structure, Differentially Influences Mother–Child Interactions in Attention‐Deficit/Hyperactivity Disorder Children With and Without Oppositional Defiant Disorder

Abstract: Objective To assess whether preschoolers with attention‐deficit/hyperactivity disorder (ADHD) behave differently during mother–child interaction tasks as a function of task palatability and whether differences are associated with the presence of comorbid oppositional defiant disorder (ODD). Methods Typically developing, ADHD, and ADHD + ODD children and their mothers participated in digitally recorded interactions, which included three 5‐min tasks, differing in level of palatability/engagement and parental str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These previous coding systems have been extensively used in research on mother–child interactions and found to be valid and reliable measures of both individual and dyadic behaviours. The new Coding System for Mother–Child Interactions has recently been evaluated in research studies, which report good intercoder reliability and therefore underline the value of this new coding system (Gopin, Healey, Grossman, Campbel, & Halperin, ; Healey et al, ; Rajendran, Kruszewski, & Halperin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous coding systems have been extensively used in research on mother–child interactions and found to be valid and reliable measures of both individual and dyadic behaviours. The new Coding System for Mother–Child Interactions has recently been evaluated in research studies, which report good intercoder reliability and therefore underline the value of this new coding system (Gopin, Healey, Grossman, Campbel, & Halperin, ; Healey et al, ; Rajendran, Kruszewski, & Halperin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The new Coding System for Mother-Child Interactions has recently been evaluated in research studies, which report good intercoder reliability and therefore underline the value of this new coding system (Gopin, Healey, Grossman, Campbel, & Halperin, 2011;Healey et al, 2010;Rajendran, Kruszewski, & Halperin, 2016).…”
mentioning
confidence: 99%